2003
DOI: 10.1300/j064v22n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Governance of Gene Action and Combining Ability for Certain Grain Quality Traits in Three Diverse Rice (Oryza sativaL.) Growing Ecosystems

Abstract: Traditional varieties or land races from diverse rice growing ecosystems serving as repository of desirable gene pools for rice improvement including rice hybrids have been marginalized or are at the verge of perhaps total genetic erosion. Biotechnology patent systems and intellectual property rights intrinsic with genetically engineered rices weigh in at odds, competing with these good grain qualified traditional rices. Genetic analyses have been made to uncover the supremacy of gene action and combining abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…Heritability values were high for all of the studied characters, suggesting the greater effectiveness of selection and improvement to be expected for these characters in future breeding programs as the genetic variance is mostly due to additive gene expression. These results are in accordance with the findings of VERMA et al, (2003), HOSSEINI et al, (2005), SHARIFI et al, (2010 a), AHMADIKHAH (2010), SUBBAIAH (2011), KARIM et al, (2007) and DINESH et al, (2011) and LIN et al, (2005). High heritability together with high GCV exhibited by grain yield, number of panicle per plant and panicle weight imply that these characters under additive gene effects and could be relied upon for further selection based on phenotypic performance (VANAJA and BABU, 2008).…”
Section: Genetic Variability Heritability and Genetic Advancesupporting
confidence: 93%
See 1 more Smart Citation
“…Heritability values were high for all of the studied characters, suggesting the greater effectiveness of selection and improvement to be expected for these characters in future breeding programs as the genetic variance is mostly due to additive gene expression. These results are in accordance with the findings of VERMA et al, (2003), HOSSEINI et al, (2005), SHARIFI et al, (2010 a), AHMADIKHAH (2010), SUBBAIAH (2011), KARIM et al, (2007) and DINESH et al, (2011) and LIN et al, (2005). High heritability together with high GCV exhibited by grain yield, number of panicle per plant and panicle weight imply that these characters under additive gene effects and could be relied upon for further selection based on phenotypic performance (VANAJA and BABU, 2008).…”
Section: Genetic Variability Heritability and Genetic Advancesupporting
confidence: 93%
“…Heritability of rice cooking quality traits has been studied also by some researchers and high heritability was indicated for amyloze content (AC) (SHARIFI et al, 2010 b). High values of heritability were also reported in yield and yield components of rice by VERMA et al, (2003) HOSSEINI et al, (2005), SHARIFI et al, (2010 a), AHMADIKHAH (2010), SUBBAIAH (2011), KARIM et al, (2007) and DINESH et al, (2011). OSMAN et al, (2012) observed high heritability coupled with high genetic advance for tillers per plant, plant height, 1000 grain weight and high heritability with low genetic advance for 50% flowering and days to maturity.…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, simultaneous improvement in important yield components and other associated traits along with grain yield may be better approach for enhancing yield potential in rice. Similar results have also been reported by Verma et al, (2003); Verma and Srivastava (2004); Saleem et al, (2010); Bagheri and Jelodar (2010) and Saidaiah et al,(2011); Sanghara and Hussain (2012); Tiwari et al, (2014); S. Prasad et al, (2015) and Archana Devi et al, (2017).…”
Section: General Combining Abilitysupporting
confidence: 78%
“…The high yielding lines discussed above having high mean performance for grain yield and for several other characters may be recommended for use as tester for developing high yielding rice hybrids in target environment that is salt affected soil (Pires et al, 2015). The success of selection in improving plant characters depends mainly on presence of substantial genetic variability (Mall et al, 2005) and nature of heritability and gene action (Verma et al, 2003). In experiment 1 the action estimates of genotype and phenotype coefficient of variation and High heritability in broad sense along with high genetic advance in percent of mean were recorded for biological yield per plant while L:B ratio should high estimates of another phenotypic coefficient of variation and high heritability in broad sense along with high genetic advance in percent of mean and showed moderate estimates of genotypic coefficient of variation.…”
Section: Resultsmentioning
confidence: 99%